Holocaust lessons for the criminal justice classroom - Sporer, Celia (Journal of Interdisciplinary Studies in Education, 2019)
The rise of antisemitic acts across the United States and worldwide and the general lack of Holocaust knowledge highlights the need to better integrate Holocaust education across disciplines, especially criminal justice. An undergraduate criminology class at Queensborough Community College (QCC) at the City University of New York (CUNY) was aligned with the goals and objectives of an on-campus exhibit, Conspiracy of Goodness, at the Kupferberg Holocaust Center. The exhibit focused on the rescuing behaviors of the village of Le Chambon during the Holocaust. Survey information suggested that prior to the class, students only had a rudimentary understanding of the Holocaust. During the semester students engaged with the exhibit, attended associated events and completed a paper comparing and contrasting the behaviors of Le Chambon with those of Jedwabne, Poland. Students selected and critically applied a criminological theory to explain the differences in behavior. Upon completion of the course, the majority of students showed an increased mastery not only of the facts of the Holocaust, but of their ability to think critically and make connections between historical events, criminological theories, and current events evidenced by their final papers, suggesting the benefit of aligning the studies of the Holocaust and criminal justice.